Retrospective Assessment of Patient and Catheter Characteristics Associated With Malpositioned Central Venous Catheters in Pediatric Patients. Issue 3 (March 2022) - Weber, Mark D.; Conlon, Thomas; Woods-Hill, Charlotte; Watts, Stephanie L.; Nelson, Eileen; Traynor, Danielle; Zhang, Bingqing; Davis, Daniela; Himebauch, Adam S.
Abstract : OBJECTIVES: The primary objective was to determine the prevalence and characteristics associated with malpositioned temporary, nontunneled central venous catheters (CVCs) placed via the internal jugular (IJ) and subclavian (SC) veins in pediatric patients. DESIGN: Single-center retrospective cohort study. SETTING: Quaternary academic PICU. PATIENTS: Children greater than 1 month to less than 18 years who had a CVC placed between January 2014 and December 2018. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: The primary outcome was the CVC tip position located on the first postprocedural radiograph. CVC tip was defined as follows: "recommended" (tip location between the carina and two vertebral bodies inferior to the carina), "high" (tip location between one and four vertebral bodies superior to the carina), "low" (tip position three or more vertebral bodies inferior to the carina), and "other" (tip grossly malpositioned). Seven hundred eighty-one CVCs were included: 481 (61.6%) were in "recommended" position, 157 (20.1%) were "high, " 131 (16.8%) were "low, " and 12 (1.5%) were "other." Multiple multinomial regression (referenced to "recommended" position) showed that left-sided catheters (adjusted odds ratio [aOR], 2.00, 95% CI 1.17-3.40) were associated with "high" CVC tip positions, whereas weight greater than or equal to 40 kg had decreased odds of having a "high" CVC tip compared with the reference (aOR, 0.45; 95% CI, 0.24–0.83). Further, weight category 20–40 kg (aOR, 2.42; 95% CI, 1.38–4.23) and females (aOR, 1.51; 95% CI, 1.01–2.26) were associated with "low" CVC tip positions. There was no difference in rates of central line–associated blood stream infection, venous thromboembolism, or tissue plasminogen activator usage or dose between the CVCs with tips outside and those within the recommended location. CONCLUSIONS: The prevalence of IJ and SC CVC tips outside of the recommended location was high. Left-sided catheters, patient weight, and sex were associated with malposition. Malpositioned catheters were not associated with increased harm.